JURISDICTIONAL CONFLICTS IN FACING COVID-19 PANDEMIC: AN ANALYSIS OF HIBAH CASES IN NEGERI SEMBILAN SYARIAH COURTS (International Seminar on Syariah and Law (INSLA), 2020)
In 2020, statistic reveals that a total number of 30 hibah cases have been registered in the Negeri Sembilan Syariah Courts. Interestingly, the total number of cases registered this year has decreased as compared to 51 cases for the previous year. This study analyses on the jurisdictions of the Syariah Courts in deciding hibah cases in Negeri Sembilan by taking into a consideration the recent outbreak of Covid-19. This study investigates the impacts of the Covid-19 pandemic on the number of hibah cases brought before the Syariah Courts in the state of Negeri Sembilan. For this purpose, this study applies a doctrinal legal approach where the data collection is based on a library-based research and the statistical data collected from Negeri Sembilan Syariah Courts. Analysis was done on several important cases concerning the jurisdiction of the courts. This study discovers that the Covid-19 pandemic has an effect on the number of registered and resolved cases pertaining to hibah in Negeri Sembilan Syariah Courts. This study recommends that electronic method such as e-proceeding to be fully implemented so as to enable the public to access the court easily. It is hoped that findings of this study will shed light on the issue of jurisdictions concerning hibah and beneficial in providing clear and precise information on the jurisdiction of the Syariah Courts in deciding hibah matters.